Semiotic Analysis and Personality of the Main Character in the Film Lady Bird and the Edge of Seventeen - Lestarai, Feby Herdini; Sundari, Hanna; Baron, Rifari (Universitas Indraprasta PGRI, 2024)
The purpose of this research is to identify semiotic data as well as the personality of the main character in the films Lady Bird and The Edge of Seventeen. The method used in this research is descriptive qualitative. This research uses Roland Barthes' Semiotics theory, which is divided into 3 types of meaning, namely Denotative, Connotative, and Myth. The data analysed are 31 visual data of Lady Bird and 33 visual data of The Edge of Seventeen. The visual data includes scene footage, facial expressions, body language, colours, clothing, and others. This research also uses the Hippocrates- Galenus Personality Typology to analyse the main characters' personalities in Lady Bird and The Edge of Seventeen, which is divided into four personality types, including Sanguinis, Phlegmatis, Choleric, and Melancholic. In the results of the analysis of the main character's personality in the film Lady Bird, 27 conversation units were foun,d consisting of 4 conversation units of sanguinis personality (17%), 13 conversation units of choleric personality (48%), and 10 conversation units of melancholic personality (37%). So it can be concluded that the main character in Lady Bird has a choleric personality. Meanwhile, the results of the personality analysis of the main character in the film The Edge of Seventeen have been found as many as 25 conversation units consisting of 8 conversation units of sanguinis personality (32%), 1 conversation unit of plegmatis personality (8%), 8 conversation units of choleric personality (32%), and 8 conversation units of melancholic personality (28%). So, it can be concluded that the main character in the film The Edge of Seventeen has a dominant sanguine and choleric personality.